A qualitative analysis of South African child offenders’ constructions of child-perpetrated crimes - Ndaba, Petronella Nobesuthu Jabulile (My University, 2020)
Debates concerning child perpetration and the potential criminal culpability of children have been the focus of attention in academia, in the media and in the public domain in recent years. Within global discursive practices, childhood has been constructed as a uniform category characterised by innocence and purity. Contrary to that, child-perpetrated crimes have been conceptualised as an anomaly, challenging the very nature of the child as innocent. In turn, such acts are classified, studied and consequently produced and reproduced, by psychology and the law, and in this way, the child offender becomes the site for intervention and treatment. The consequential discourse on child violence and perpetrated crime is rearticulated in public domains such as the media which plays an important role in maintaining and challenging hegemonic discourse pertaining to childhood perpetration. This study therefore, through qualitatively engaging with male and female child offenders aged between 14and 18-years old, explored the discourses that child-perpetrators employ to (re)construct and hence engage in child-perpetrated crimes. From this, four themes emerged that locates the child offender within local discursive practices; conditions that produce conceivable childhood criminality, constructions of childhood, gendered and institutionalised discourses. The aforementioned surfaced a South African child offender who engaged in a constant negotiation between childhood and adulthood. This being the very vehicle that allowed participants to commit crimes but seemingly deny doing so. Constructions of childhood(re) articulated the incapacity of childhood criminality while adulthood and occupying adult-like qualities served as a discursive strategy utilised by child offenders to demonstrate their criminality. Theoretically, this study (re)articulates normative constructions of childhood and the aetiology underpinning child-perpetration but also simultaneously makes visible a context specific child offender who occupies alternate subject positions. Thus, the implication of this study lies in contemporary constructions of culpability and future typologies of child offenders; both of which need to integrate understanding the discursive strategies utilised by child offenders in-situ to realise their criminality
This research report is submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg in partial fulfilment of the degree Master of Arts in Social and Psychological Research by Coursework and Research Report, 2020